ChemInform Abstract: Acid‐Catalyzed Direct Conjugate Alkenylation of α, β‐Unsaturated Ketones. Issue 10 (11th March 2014) - Okamoto, Kazuhiro; Tamura, Eisuke; Ohe, Kouichi
Abstract Treatment of the product (IIIa) with HBF4 gives the compound (IV) via 1, 4‐phenyl shift.